The Economics of Immortality: The Demi-Immortal Oriental, Enlightenment Vitalism, and Political Economy in Dracula - J. Jeffrey Franklin (Cahiers Victoriens et Edouardiens)
Dracula has fulfilled the ambition of Dracula: it has colonized and enthralled the industrial and post-industrial Western world, achieved the integration into modern free-market capitalism that its namesake was unable to achieve. The outpouring of Dracula scholarship in the past twenty years likewise testifies to the vampire’s cultural and economic success. Intending to add a new interpretation to this long list, the current essay argues, first, that Dracula belongs to a character-type that I will define as the “demi-immortal Oriental.” This character type began appearing with increasing frequency in the early nineteenth century for a range of specific historical reasons stemming from the Enlightenment, the Industrial Revolution, and Romanticism, but I will focus, secondly, on one specific historical precedent, namely “Enlightenment vitalism” and its subsequent expression as Mesmeric vitalism. Third, I will argue that in the character of the demi-immortal Oriental vitalism came to signify a type of eternal life in competition with the traditional Judeo-Christian afterlife, which rendered it necessarily damnable. The essay then draws out a parallel within Dracula between this demi-immortality and a specific economic model for which Dracula also is a figure. In Halberstam’s terms, two of the monsters that late-Victorian ideologies wanted to disavow were any form of immortality other than the traditional Christian one and any form of economics other than Adam Smith’s naturally free circulation and exchange. Two monstrous alternatives—demi-immortality and an archaic economy of gold and land—are wedded in/as Dracula. Finally, I will delineate a counter-argument, both to my own preceding argument and to that most common among criticisms of the novel, that Dracula, far from being the anti-capitalist anti-Christ, is at once both more spiritual and truer to laissez-faire economics than the vampire slayers who purportedly defend those very values.